Evaluation of the efficacy of enteral therapy in a patient with posttraumatic pancreatitis (clinical case) - M. S. Zhigalova; V. V. Kiselev; S. S. Petrikov; P. A. Yartsev; A. A. Ryk; Yu. S. Teterin; N. V. Shavrina; I. E. Selina; M. M. Rogal; K. V. Staleva (Вестник анестезиологии и реаниматологии)
Introduction. In the development of post-traumatic pancreatitis, an important role is played by microcirculatory disorders, developing against the background of inflammation and decreased capillary blood flow not only in the tissues of the pancreas, but also in other organs, including the intestine, which leads to neuroendocrine dysregulation, dysfunction and/or death of intestinal epithelial cells, disruption of the motor and evacuation functions of the intestine, and, as a consequence, the development of intestinal insufficiency syndrome.The objective was to demonstrate the effectiveness of enteral therapy in a patient with a closed abdominal injury, liver injury and posttraumatic pancreatitis.Materials and methods. We analyzed a clinical case of hospitalization of patient K., 38 years old, with the following diagnosis: “Closed abdominal trauma. Liver trauma of the S6 segment. Hemoperitoneum 1000 ml. Complication: right-sided segmental pneumonia. Bilateral hydrothorax. Posttraumatic pancreatitis”. The patient was admitted with complaints of upper abdominal pain and nausea two weeks after blunt abdominal trauma. She was treated as an outpatient. During the last two days she started to notice nausea, increased pain syndrome in the right side and upper parts. She was brought by an ambulance. Hybrid surgical intervention was performed: endovascular celiacography, superselective embolization of the right hepatic artery branch and diagnostic videolaparoscopic sanation and drainage of the abdominal cavity. In the postoperative period, treatment was performed according to the National Clinical Guidelines, supplemented with enteral therapy.Conclusion. This clinical observation demonstrated the effectiveness of including enteral therapy in a complex of therapeutic measures in the patient with closed abdominal trauma, liver trauma, posttraumatic pancreatitis, which was expressed in a decrease in the level of lactate, alanine aminotransferase, aspartate aminotransferase, lactate dehydrogenase, C-reactive protein, leukocytes on the 3rd day of dynamic observation. At the same time, an increase in the absolute number of lymphocytes, the concentration of total protein and albumin was noted. The proposed scheme contributed to the regression of signs of intestinal insufficiency syndrome, normalization of intra-abdominal pressure by the 7th postoperative day, prevention of the development of purulent-septic complications and multiple organ failure, a successful outcome of hospitalization.